Dating jitters, a study and guide to CG hair - Lim, Emmanuel Bao Qun (2018)
Dating Jitters is a Final Year Project in the form of a visual effects film headed by a group of four students, including myself. One of my responsibilities included the creation of the computer generated characters fur which is the topic of this report. This report mainly follows my development process starting from initial attempts and analysis of said attempts, followed by secondary attempts learning from my analysis, and finally a guide to my work flow which have been found to be effective in producing relatively good results. In addition, this report would include studies on understanding why hair looks the way it does and what to look out for when recreating a hairstyle based on references.